A double-layer protective waterproof busbar

The double-layer outer sheath is prepared by coextrusion and self-crosslinking technology, and the use of homemade water supply antioxidants, the problems of existing waterproof jelly bar material limitation and poor interlayer compatibility are solved, achieving better sealing and performance.

CN119132709BActive Publication Date: 2025-02-28GUANGDONG RIZHAO ELECTRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411043223.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-02-28
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

During the manufacturing process, existing waterproof jelly wires have problems such as material limitations, insufficient single layer protection and poor interlayer compatibility, resulting in poor sealing and poor performance.

Method used

A double-layer outer sheath was prepared by coextruding linear low-density polyethylene and high-density polyethylene and self-crosslinking at room temperature, and a homemade water-supply antioxidant was used to improve oxidation resistance and compatibility.

Benefits of technology

The sealing and connectivity of double-layer protection is achieved, cost and energy consumption is reduced, and the problem of interlayer cracks is avoided, while improving the mechanical properties and oxidation resistance of the outer sheath are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a novel double-layer protective waterproof busbar, which belongs to the technical field of power transmission equipment. The double-layer protective waterproof busbar comprises an aluminum tube, a copper tube, a conductor shielding layer, a main insulating layer, an insulating shielding layer, a grounding screen, and a double-layer outer sheath, wherein the double-layer outer sheath is composed of an inner sheath and an outer sheath, and the inner sheath comprises 85-95 parts of linear low-density polyethylene, 8-15 parts of ethylene-octene elastomer, 2.3-2.7 parts of silane coupling agent, 0.12-0.15 parts of initiator, 0.5-1 parts of antioxidant, 1.2-1.5 parts of stearic acid, 3-3.5 parts of zinc oxide, 2.4-2.8 parts of catalyst; the outer sheath comprises 50-70 parts of linear low-density polyethylene, 40-60 parts of high-density polyethylene, 2.3-2.7 parts of silane coupling agent, 0.12-0.15 parts of initiator, 2.5-3.0 parts of water-supply type antioxidant, 1.2-1.5 parts of zinc oxide, and 2.4-2.8 parts of catalyst; the present invention also discloses a method for preparing a novel double-layer protective waterproof busbar, by co-extrusion and self-crosslinking methods, a double-layer outer sheath with excellent single-layer performance, good compatibility between layers, and strong adhesion is extruded onto a pre-prepared busbar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of power transmission equipment, and in particular relates to a novel double-layer protective waterproof busbar. Background Art

[0002] Existing waterproof busbars usually embed the conductive bars of each phase in the resin insulator of the overall structure, so that the conductive bars and the resin insulator are consolidated into a waterproof whole. The manufacturing process usually adopts a casting method, which limits the range of materials used, and most of them can only provide single-layer protection. As an advanced protection method, double-layer protection has the advantages of good insulation performance, excellent mechanical properties, and good waterproof effect. At present, the preparation process of the double-layer outer sheath of the busbar is relatively immature. The compatibility between layers and the different expansion coefficients between different materials will lead to problems such as separation between layers and poor sealing.

[0003] Polyethylene has good processing properties, mechanical properties and dielectric properties, and stands out among many polymers as cable materials. With the development of cross-linked polyethylene technology, cross-linked polyethylene cables have gradually been widely used in power systems due to their excellent mechanical and electrical properties and simple manufacturing process. In the manufacture of traditional silane cross-linked polyethylene, the cable material has to be soaked in warm water or steam for a long time, which makes the production process of cross-linked polyethylene time-consuming, labor-intensive and energy-consuming; in addition, it also faces problems such as water ingress and uneven cross-linking during the soaking process. The emergence of self-cross-linking technology not only provides a new solution to this problem, but also finds a solution to the problem of poor compatibility between the layers of the double-layer protective busbar. At present, most self-cross-linking uses a water supply agent that is a combination of organic acid and zinc oxide. While producing water, the organic acid zinc obtained is a water-absorbing compound, which will lead to a decrease in the water supply performance of the water supply agent, and the organic acid zinc produced will also affect the performance of the cable. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention adopts a method of co-extrusion of linear low-density polyethylene and high-density polyethylene and then self-crosslinking at room temperature to prepare a double-layer outer sheath of cross-linked polyethylene material, solves the problem of interlayer separation by covalent crosslinking, and adopts a homemade water-supply type antioxidant. On the one hand, the amount of zinc oxide used is reduced, reducing the influence of excessive organic acid zinc on material properties, and on the other hand, the compatibility of the antioxidant with the polyethylene material is improved, thereby improving the mechanical properties and antioxidant properties of the outer sheath.

[0005] The technical scheme of the present invention is as follows: a novel double-layer protective waterproof busbar, comprising an aluminum tube, a copper tube, a conductor shielding layer, a main insulating layer, an insulating shielding layer, a grounding screen, and a double-layer outer sheath, characterized in that the double-layer outer sheath comprises an inner sheath and an outer sheath, and the raw materials of the inner sheath, by weight, include 85 to 95 parts of linear low-density polyethylene, 8 to 15 parts of ethylene-octene elastomer, 2.3 to 2.7 parts of silane coupling agent, 0.12 to 0.15 parts of initiator, and 0.5 to 1.5 parts of antioxidant. 1 part, 1.2-1.5 parts of stearic acid, 3-3.5 parts of zinc oxide, and 2.4-2.8 parts of catalyst; the raw materials of the outer sheath, by weight, include 50-70 parts of linear low-density polyethylene, 40-60 parts of high-density polyethylene, 2.3-2.7 parts of silane coupling agent, 0.12-0.15 parts of initiator, 2.5-3.0 parts of water-supply antioxidant, 1.2-1.5 parts of zinc oxide, and 2.4-2.8 parts of catalyst; the water-supply antioxidant has the following molecular structure of Formula I:

[0006]

[0007] Preferably, the silane coupling agent is at least one of vinyltriethoxysilane and vinyltrimethoxysilane; the initiator is dicumyl peroxide; and the catalyst is dibutyltin dilaurate.

[0008] More preferably, the silane coupling agent is vinyltrimethoxysilane.

[0009] The outer sheath in the double-layer outer sheath often requires better mechanical strength, wear resistance, and heat resistance, especially anti-oxidation and anti-ultraviolet anti-aging capabilities. Therefore, we designed a water-supply antioxidant, which reduces the amount of zinc oxide and stearic acid on the one hand and enhances the compatibility of the antioxidant with the polyethylene material on the other hand, thereby improving the comprehensive performance of the outer sheath. The water-supply antioxidant is obtained by the following steps: Under a nitrogen atmosphere, 1.1 to 1.3 eq of a dianhydride compound is added to a reactor, dissolved in chloroform, 2.5 to 3.0 eq of an amine catalyst is added, and 1.0 eq of 2,2,6,6-tetramethylpiperidinamine is added to the reactor at room temperature for 8 to 16 hours. After the reaction is stopped, the mixture is washed three times with an aqueous sodium hydroxide solution and three times with a saturated ammonium chloride solution, and the organic phase is collected and evaporated to obtain a water-supply antioxidant.

[0010] It should be noted that the concentration of the sodium hydroxide aqueous solution is 1-2 mol / L.

[0011] Preferably, the dianhydride compound is one or more of tetrahydrophthalic anhydride, exo-3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride, and 3a,4,7,7a-tetrahydro-4,7-epoxyisobenzofuran-1,3-dione; and the amine catalyst is at least one of triethylamine and N,N-diisopropylethylamine.

[0012] More preferably, the dianhydride compound is tetrahydrophthalic anhydride; and the amine catalyst is N,N-diisopropylethylamine.

[0013] The present invention also protects a method for preparing the novel double-layer protective waterproof busbar, comprising the following steps:

[0014] S1. Pre-preparation of inner sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into a 70-90°C oven and dry them for 10-12 hours, then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the antioxidant and stearic acid, and one part is mixed with zinc oxide, and they are placed in sealed containers and allowed to stand for 18-24 hours, and then extruded by a twin-screw extruder in turn to obtain mixed masterbatch A;

[0015] S2. Pre-preparation of outer sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and high-density polyethylene into a 70-90°C oven and dry them for 10-12 hours, then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the water-supply type antioxidant, and one part is mixed with zinc oxide, and they are placed in sealed containers and allowed to stand for 18-24 hours, and then extruded by a twin-screw extruder in turn to obtain a mixed masterbatch B;

[0016] S3. Busbar pre-preparation: put the aluminum tube and the copper tube into the mold, wrap the shielding layer, extrude the insulating material to form the main insulating layer, wrap the insulating shielding layer, and wrap the grounding screen to prepare the busbar;

[0017] S4. New double-layer protective waterproof busbar: Add mixed masterbatch A and mixed masterbatch B to the preheated single-screw extruder 1 and single-screw extruder 2 respectively, start the single-screw extruder 1, and after the inner layer material flows out stably, start the single-screw extruder 2, and use a double-layer co-extrusion head to extrude the double-layer structure onto the pre-prepared busbar obtained in step S3. After cooling in a water bath, fix the extruded material and place it in a humid environment at room temperature for 3 to 4 days. After completing the self-cross-linking process of the polyethylene, dry it to obtain a new double-layer protective waterproof busbar.

[0018] Preferably, the parameters of the twin-screw extruder in steps S1 and S2 are: temperature of the first section 75-85°C, the second section 85-95°C, the third section 95-105°C, the fourth section 115-125°C, the fifth section 135-145°C, the die head 155-165°C; the main engine speed is 200-240r / min, and the feeding speed is 20-25r / min.

[0019] Preferably, the parameters of the single screw extruder 1 in step S3 are a temperature of 165-170°C in the first section, 175-180°C in the second section, 185-190°C in the third section, 195-200°C in the fourth section, and a main engine speed of 30-40r / min; the parameters of the single screw extruder 2 are a temperature of 170-175°C in the first section, 185-190°C in the second section, 190-195°C in the third section, 200-210°C in the fourth section, and a main engine speed of 30-40r / min.

[0020] Preferably, the thickness of the double-layer co-extrusion die head in step S3 is set to 3-7 mm for the inner layer and 2-3 mm for the outer layer.

[0021] Beneficial Effects

[0022] The present invention adopts a method of preparing a double-layer outer sheath of cross-linked polyethylene material by co-extruding linear low-density polyethylene and high-density polyethylene and then self-crosslinking at room temperature, which has the following beneficial effects compared with the prior art:

[0023] 1) Double-layer protection is adopted. The inner sheath adopts linear low-density polyethylene that provides excellent electrical insulation and good flexibility, and the outer sheath adopts part of high-density polyethylene to provide better mechanical protection, wear resistance and chemical resistance. The inner sheath is thicker and adopts cheaper linear low-density polyethylene, and the outer sheath is thinner and adopts part of higher-value high-density polyethylene to reduce costs. It is prepared by double-layer co-extrusion process, which has better sealing, connectivity and higher efficiency than multi-step lamination process and coating technology.

[0024] 2) The two layers use polyethylene materials of different densities as double-layer protective materials to enhance the compatibility between the materials; cross-linked polyethylene is obtained by self-crosslinking, which reduces costs and saves energy consumption. At the same time, the adhesion between the inner sheath and the outer sheath is further strengthened by covalent crosslinking, without the need to add additional compatibilizers, which further saves costs; cross-linking through high-temperature cooking is avoided, and the problem of cracks between layers caused by uneven heating and different expansion coefficients is avoided.

[0025] 3) Self-made water-supply antioxidants are used to replace stearic acid and reduce the amount of zinc oxide used. On the other hand, the compatibility of the antioxidant with the polyethylene material is enhanced, thereby improving the overall performance of the outer sheath. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the overall structure of the present invention;

[0027] In the figure: 100. aluminum tube, 101. copper tube, 102. conductor shielding layer, 103. main insulation layer, 104. insulation shielding layer, 105. grounding screen, 106. double outer sheath;

[0028] Figure 2 This is the synthesis step of the water-supply type antioxidant of the present invention;

[0029] Figure 3 This is the nuclear magnetic hydrogen spectrum of the water-supply antioxidant of the present invention;

[0030] Figure 4 This is the water production and self-crosslinking mechanism of the double-layer outer sheath of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0033] The raw materials and equipment used in the embodiments and comparative examples are described as follows:

[0034] Linear low-density polyethylene: brand DFDA-7042, purchased from Wuhan Rongchuang Plastic Co., Ltd.;

[0035] High-density polyethylene: item number 5000S, purchased from Dongguan Shenghua Plastic Raw Materials Co., Ltd.;

[0036] Ethylene-octene elastomer: brand 8999, purchased from Dongguan Yucheng Plastic Chemical Co., Ltd.;

[0037] Silane coupling agent: Product No. ZB190, purchased from Hubei Zhenbo Chemical Co., Ltd.;

[0038] Initiator: dicumyl peroxide, purchased from Tianjin Chemical Reagent Factory No. 1;

[0039] Antioxidant: Antioxidant 1010, purchased from Dongguan Guangsiyuan Polyurethane Materials Co., Ltd.;

[0040] Stearic acid: Product No. CH0537, purchased from Hubei Chenghai Chemical Co., Ltd.;

[0041] Zinc oxide: Product No. A0820065, purchased from Dongguan Qiaoke Chemical Co., Ltd.;

[0042] Catalyst: Product No. 2022062710, purchased from Tesco Chemical Co., Ltd.;

[0043] Dianhydride compound: Product No. A48608, purchased from Hunan Wokai Biotechnology Co., Ltd.;

[0044] 2,2,6,6-Tetramethylpiperidinamine: Product number: BD0063, purchased from Hubei Baidu Chemical Co., Ltd.

[0045] Water supply antioxidant

[0046] Under a nitrogen atmosphere, 1.2 eq of a dianhydride compound (tetrahydrophthalic anhydride, product number A48608, purchased from Hunan Wokai Biotechnology Co., Ltd.) was added to the reactor and dissolved in chloroform. After adding 2.5 eq of N,N-diisopropylethylamine, 1.0 eq of 2,2,6,6-tetramethylpiperidinamine was added to the reactor at room temperature and reacted for 12 hours. The reaction was stopped, and the mixture was washed three times with an aqueous sodium hydroxide solution and three times with a saturated ammonium chloride solution. The organic phase was collected and evaporated to obtain a water-supplying antioxidant 1.

[0047] A method for preparing a double-layer outer sheath comprises the following steps:

[0048] S1. Pre-preparation of inner sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into an oven at 80°C for 12 hours, and then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the antioxidant and stearic acid, and one part is mixed with zinc oxide, and they are placed in sealed containers and allowed to stand for 20 hours. A twin-screw extruder is used, with the first section at 80°C, the second section at 90°C, the third section at 100°C, the fourth section at 120°C, the fifth section at 140°C, and the die at 160°C; the main engine speed is 230r / min, the feeding speed is 24r / min, and the mixed masterbatch A is obtained by extrusion and mixing;

[0049] S2. Pre-preparation of outer sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and high-density polyethylene into an oven at 80°C for 12 hours and then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the water-supply type antioxidant, and one part is mixed with zinc oxide, and they are placed in sealed containers and allowed to stand for 20 hours. A twin-screw extruder is used, with the first section at 80°C, the second section at 90°C, the third section at 100°C, the fourth section at 120°C, the fifth section at 140°C, and the die at 160°C; the main engine speed is 230r / min, the feeding speed is 24r / min, and the mixed masterbatch B is obtained by extrusion and mixing;

[0050] S3. Preparation of a double-layer outer sheath: Add the mixed masterbatch A and the mixed masterbatch B to the preheated single-screw extruder 1 and the single-screw extruder 2 respectively, start the single-screw extruder 1, the parameters are the temperature of the first section 165°C, the second section 175°C, the third section 185°C, the fourth section 195°C, the main engine speed 40r / min, after the inner layer material flows out stably, start the single-screw extruder 2, the parameters are the temperature of the first section 175°C, the second section 190°C, the third section 195°C, the fourth section 210°C, the main engine speed 40r / min, and use a double-layer co-extrusion head to extrude a double-layer structure, the inner layer is 7mm, and the outer layer is 3mm. After cooling in a water bath, the extruded material is fixed and placed in a humid environment at room temperature for 4d. After completing the self-crosslinking process of the polyethylene, it is dried to obtain a double-layer outer sheath.

[0051] Table 1 Inner sheath and outer sheath formula (mass / kg)

[0052]

[0053] Example 1

[0054] The mixed masterbatch A1 and the mixed masterbatch B1 are obtained through step S3.

[0055] Example 2

[0056] The mixed masterbatch A1 and the mixed masterbatch B2 are obtained through step S3.

[0057] Example 3

[0058] The mixed masterbatch A1 and the mixed masterbatch B3 are obtained through step S3.

[0059] Example 4

[0060] The mixed masterbatch A2 and the mixed masterbatch B1 are obtained through step S3.

[0061] Example 5

[0062] The mixed masterbatch A2 and the mixed masterbatch B2 are obtained through step S3.

[0063] Example 6

[0064] The mixed masterbatch A2 and the mixed masterbatch B3 are obtained through step S3.

[0065] Example 7

[0066] The mixed masterbatch A3 and the mixed masterbatch B1 are obtained through step S3.

[0067] Example 8

[0068] The mixed masterbatch A3 and the mixed masterbatch B2 are obtained through step S3.

[0069] Example 9

[0070] The mixed masterbatch A3 and the mixed masterbatch B3 are obtained through step S3.

[0071] Comparative Example 1

[0072] The mixed masterbatch A3 and the mixed masterbatch B4 are obtained through step S3.

[0073] Comparative Example 2

[0074] The mixed masterbatch A3 and the mixed masterbatch B5 are obtained through step S3.

[0075] Comparative Example 3

[0076] The mixed masterbatch A3 and the mixed masterbatch B3 are prepared by the following steps: the mixed masterbatch A3 and the mixed masterbatch B3 are added into the preheated single screw extruder 1 and the single screw extruder 2 respectively; the single screw extruder 1 is started with the parameters of the temperature of the first section 165°C, the second section 175°C, the third section 185°C, the fourth section 195°C, and the main engine speed 40r / min; after cooling in a water bath, the obtained extruded material is fixed and placed in a humid environment at room temperature for 4d; the single screw extruder 2 is started with the parameters of the temperature of the first section 175°C, the second section 190°C, the third section 195°C, the fourth section 210°C, and the main engine speed 40r / min; the inner layer material is extruded, and the material is placed in a humid environment at room temperature for 4d, and dried to obtain a double-layer outer sheath.

[0077] Comparative Example 4

[0078] Compared with step S3, the difference between mixed masterbatch A3 and mixed masterbatch B3 is that the cross-linking is carried out by water bath cooling and steaming for 12 hours at a water temperature of 80 degrees Celsius.

[0079] The following is the test method of the performance parameters involved in the present invention:

[0080] (1) NMR data: 400 MHz NMR instrument (Bruker, Germany);

[0081] (2) Tensile strength: The extruder was changed to a die with a 0.5 mm sheet, and the inner and outer sheath materials were tested according to GB / T 2951.11-2008 “General test methods for insulation and sheath materials for electric and optical cables”;

[0082] (3) Elongation at break: The extruder die is 0.5 mm sheet, and the inner and outer sheath materials are tested according to GB / T 2951.11-2008 “General test methods for insulation and sheath materials of electric and optical cables”;

[0083] (4) Shore hardness: The extruder die is 4 mm thick. The inner and outer sheath materials are tested according to GB / T 2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester";

[0084] (5) Dielectric constant: Cut into 100mm*100mm*1mm sheets and measure the inner and outer sheath materials according to GBT 31838.6-2021 "Solid Insulating Materials: Dielectric and Resistance Properties"

[0085] (6) Heat aging performance: (135°C for 168 h) Determined according to GB 2591.7 method.

[0086] (7) Water seepage test: measured according to GB T17737.203-2018 "Coaxial communication cables Part 1-203: Environmental test methods - Water seepage test for cables";

[0087] (8) Water absorption percentage: Cut the inner and outer sheath pipes with a length of 25 mm respectively and measure according to GB 1034-2008 "Plastics - Determination of water absorption";

[0088] (9) Peel force: measured according to GB / T 8808-1988 “Peel test method for soft composite plastic materials”.

[0089] The preparation method of the sample in test methods (2) to (7) is to add the mixed masterbatch A and the mixed masterbatch B to the preheated single screw extruder 1 and the single screw extruder 2 respectively, start the single screw extruder 1, the parameters are the temperature of the first section 165℃, the second section 175℃, the third section 185℃, the fourth section 195℃, and the main engine speed 40r / min, start the single screw extruder 2, the parameters are the temperature of the first section 175℃, the second section 190℃, the third section 195℃, the fourth section 210℃, and the main engine speed 40r / min, both single screw extruders use a sheet extruder head, after cooling in a water bath, the obtained extruded material is fixed and placed in a humid environment at room temperature for 4d, and the test is performed after the self-crosslinking process of polyethylene is completed. Test methods (8) to (9) are the same as step S3.

[0090] Table 2 Physical properties of inner and outer sheaths

[0091]

[0092] Table 3 Bonding ability between inner sheath and outer sheath

[0093]

[0094] From the data in Table 2, it can be seen that the inner sheath has a higher elongation at break and a smaller dielectric constant, and has better electrical insulation performance and flexibility. The inner layer contains less antioxidant, and the change rate of elongation at break and the change rate of tensile strength are higher. The outer sheath has higher tensile strength and Shore hardness, and lower water absorption percentage, change rate of elongation at break and change rate of tensile strength. As the outer layer, it has better mechanical protection, wear resistance, waterproof and oxidation resistance. From the data of mixed masterbatches B3 and B4, it can be seen that the physical properties of the homemade water-supply antioxidant are reduced by using the same quality of antioxidants and water-supply agents. The addition of too much zinc oxide and stearic acid will lead to an increase in the water absorption of the outer layer. From the data of mixed masterbatch B5, it can be seen that excessive addition of water-supply antioxidants will lead to a decrease in material performance.

[0095] It can be seen from the data of Examples 1 to 9 in Table 3 that the peeling force between the prepared double-layer outer sheaths is greater than 20N / cm, which indicates that the two layers have excellent bonding ability. It can be seen from the data of Comparative Example 1 that the peeling force between the prepared double-layer outer sheaths is reduced by replacing the homemade water-supply antioxidant with the same mass of antioxidant and water-supply agent; it can be seen from Comparative Example 2 that excessive addition of water-supply antioxidant has little effect on the bonding ability between the double-layer outer sheaths; it can be seen from the data of Comparative Example 3 that the peeling force between the double-layer outer sheaths prepared without the double-layer co-extrusion process is greatly reduced, and the bonding ability between the two layers is reduced; it can be seen from the data of Comparative Example 4 that cross-linking by steaming will cause uneven heating of the material, thereby causing cracks to form due to differences in expansion.

[0096] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A double-layer protective waterproof busbar, comprising an aluminum tube, a copper tube, a conductor shielding layer, a main insulating layer, an insulating shielding layer, a grounding screen, and a double-layer outer sheath, characterized in that: The double-layer outer sheath comprises an inner sheath and an outer sheath. The raw materials of the inner sheath, by weight, comprise 85-95 parts of linear low-density polyethylene, 8-15 parts of ethylene-octene elastomer, 2.3-2.7 parts of silane coupling agent, 0.12-0.15 parts of initiator, 0.5-1 parts of antioxidant, 1.2-1.5 parts of stearic acid, 3-3.5 parts of zinc oxide, and 2.4-2.8 parts of catalyst; the raw materials of the outer sheath, by weight, comprise 50-70 parts of linear low-density polyethylene, 40-60 parts of high-density polyethylene, 2.3-2.7 parts of silane coupling agent, 0.12-0.15 parts of initiator, 2.5-3.0 parts of water-supply antioxidant, 1.2-1.5 parts of zinc oxide, and 2.4-2.8 parts of catalyst; the water-supply antioxidant has the following molecular structure of Formula I:

2. The double-layer protective waterproof busbar according to claim 1, characterized in that: The silane coupling agent is at least one of vinyl triethoxysilane and vinyl trimethoxysilane; the initiator is dicumyl peroxide; and the catalyst is dibutyltin dilaurate.

3. The double-layer protective waterproof busbar according to claim 1, characterized in that: The water supply type antioxidant is obtained by the following steps: Under a nitrogen atmosphere, 1.1 to 1.3 eq of a dianhydride compound was added to a reactor, dissolved in chloroform, 2.5 to 3.0 eq of an amine catalyst was added, and then 1.0 eq of 2,2,6,6-tetramethylpiperidinamine was added to the reactor at room temperature. After reacting for 8 to 16 hours, the reaction was stopped, and the mixture was washed three times with an aqueous sodium hydroxide solution and three times with a saturated ammonium chloride solution. The organic phase was collected and evaporated to obtain a water-supplying antioxidant.

4. The double-layer protective waterproof busbar as claimed in claim 3, characterized in that The dianhydride compound is one or more of tetrahydrophthalic anhydride, exo-3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride, and 3a,4,7,7a-tetrahydro-4,7-epoxyisobenzofuran-1,3-dione; and the amine catalyst is at least one of triethylamine and N,N-diisopropylethylamine.

5. The method for preparing a double-layer protective waterproof busbar according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Pre-preparation of inner sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into a 70-90°C oven and dry them for 10-12 hours, then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the antioxidant and stearic acid, and one part is mixed with zinc oxide, and they are placed in sealed containers and allowed to stand for 18-24 hours, and then extruded by a twin-screw extruder in turn to obtain mixed masterbatch A; S2. Pre-preparation of outer sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and high-density polyethylene into a 70-90°C oven and dry them for 10-12 hours, then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the water-supply type antioxidant, and one part is mixed with zinc oxide, and they are placed in sealed containers and allowed to stand for 18-24 hours, and then extruded by a twin-screw extruder in turn to obtain a mixed masterbatch B; S3. Busbar pre-preparation: put the aluminum tube and the copper tube into the mold, wrap the shielding layer, extrude the insulating material to form the main insulating layer, wrap the insulating shielding layer, and wrap the grounding screen to prepare the busbar; S4. Double-layer protective waterproof busbar: Add mixed masterbatch A and mixed masterbatch B to the preheated single-screw extruder 1 and single-screw extruder 2 respectively, start the single-screw extruder 1, and after the inner layer material flows out stably, start the single-screw extruder 2, and use a double-layer co-extrusion head to extrude the double-layer structure onto the pre-prepared busbar obtained in step S3. After cooling in a water bath, fix the extruded material and place it in a humid environment at room temperature for 3 to 4 days. After completing the self-cross-linking process of the polyethylene, dry it to obtain a double-layer protective waterproof busbar.

6. The method for preparing a double-layer protective waterproof busbar according to claim 5, characterized in that: The parameters of the twin-screw extruder in steps S1 and S2 are as follows: the temperature of the first section is 75-85°C, the second section is 85-95°C, the third section is 95-105°C, the fourth section is 115-125°C, the fifth section is 135-145°C, the die head is 155-165°C; the main engine speed is 200-240r / min, and the feeding speed is 20-25r / min.

7. The method for preparing a double-layer protective waterproof busbar according to claim 5, characterized in that: The parameters of the single screw extruder 1 in step S4 are as follows: the temperature of the first section is 165-170°C, the second section is 175-180°C, the third section is 185-190°C, the fourth section is 195-200°C, and the main engine speed is 30-40r / min; the parameters of the single screw extruder 2 are as follows: the temperature of the first section is 170-175°C, the second section is 185-190°C, the third section is 190-195°C, the fourth section is 200-210°C, and the main engine speed is 30-40r / min.

8. The method for preparing a double-layer protective waterproof busbar according to claim 5, characterized in that: The thickness of the double-layer co-extrusion die head described in step S4 is set to 3-7 mm for the inner layer and 2-3 mm for the outer layer.

Citation Information

Patent Citations

  • Aerial insulated cable cross linked polyethylene insulation material containing graphene and cable

    CN104992754A

  • Copper core mica tape mineral insulated corrugated copper sheathed power cable

    CN109801754A